Transformation of the Transaction Cost and the Agency Cost in an Organization and the Applicability of Blockchain—A Case Study of Peer-to-Peer Insurance - Sun, Ruo-Ting; Garimella, Aravinda; Han, Wencui; Chang, Hsin-Lu; Shaw, Michael J. (Frontiers in Blockchain, 2020)
Blockchain supports a variety of decentralized applications enabled by its immutable, decentralized, and trustless properties. However, there are no unifying criteria for blockchain architecture across the organizations and business models. This variance has created complex and diverse blockchain products. Costs in every economic exchange with partners are associated with two metrics: transaction costs due to market imperfections and agency costs due to conflict of interest and information asymmetry in an organization. To understand the effectiveness of economic activities by blockchain intervention and facilitate strategic alignment, we use transaction cost and agency cost as theoretical lenses to explore the impacts of blockchain, discuss the transformation of those costs, and support our arguments using a case study. Our study proposes that blockchain technology brings two more benefits, trust and transparency, to the existing Internet-based business services, and helps improve corporate governance. Smart contracts improve the execution time of transactions significantly and increase transaction volume rapidly. As the internet shifts hierarchies towards electronic markets, lack of trust between peers inhibits exchanges. Blockchain applications provide a framework for building trust between peers through its consent mechanism, which allows organizations to construct trust and operate in a more decentralized manner. Thus, by including blockchain in the current Internet infrastructure, the decision boundary of organization forms would extend outward. Finally, the transformation of costs in different stages of the blockchain transition, as described in our study, has important managerial implications for the organization structure and the role of third parties. Blockchain does not assume away transaction and agency costs but pushes the transformation of the two, forming a more efficient economic entity. This study contributes to the academia and the industry. We first add to the understanding of blockchain from the perspective of exchange technology. Second, we contribute to the prediction of organization boundaries. Third, the shift in the role of third parties supports the transaction cost theory in terms of controlling opportunism. Lastly, this study facilitates the development of blockchain business models and contributes to the practice.